Apoptosis in Renal Proximal Tubules of Rats Treated with Low Doses of Aminoglycosides - El Mouedden, Mohammed (American Society for Microbiology, 2000)
Kidney cortex apoptosis was studied with female Wistar rats treated for 10 days with gentamicin and netilmicin at daily doses of 10 or 20 mg/kg of body weight and amikacin or isepamicin at daily doses of 40 mg/kg. Apoptosis was detected and quantitated using cytological (methyl green-pyronine) and immunohistochemical (terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling) staining, in parallel with a measurement of drug-induced phospholipidosis (cortical phospholipids and phospholipiduria), cortical proliferative response ((3)H incorporation in DNA and histoautoradiography after in vivo pulse-labeling with [(3)H]thymidine), and kidney dysfunction (blood urea nitrogen and creatinine). Gentamicin induced in proximal tubules a marked apoptotic reaction which (i) was detectable after 4 days of treatment but was most conspicuous after 10 days, (ii) was dose dependent, (iii) occurred in the absence of necrosis, and (iv) was nonlinearly correlated with the proliferative response (tubular and peritubular cells). Comparative studies revealed a parallelism among the extents of phospholipidosis, apoptosis, and proliferative response for three aminoglycosides (gentamicin >> amikacin ≅ isepamicin). By contrast, netilmicin induced a marked phospholipidosis but a moderate apoptosis and proliferative response. We conclude that rats treated with gentamicin develop an apoptotic process as part of the various cortical alterations induced by this antibiotic at low doses. Netilmicin, and still more amikacin and isepamicin, appears safer in this respect. Whereas a relation between aminoglycoside-induced tubular apoptosis and cortical proliferative response seems to be established, no simple correlation with phospholipidosis can be drawn.